Degradations of semiconductor devices under pulsed heat overloading - Chumakov, V.I. (Вопросы атомной науки и техники, 2000)
The linear heat model of degradations of semiconductor devices under pulsed electric overloading has been constructed. Expressions for temporal dependencies of the temperature under different forms of pulse of current are obtained.